Composition of the Steam Volatile Oil from Hyptis suaveolens Poit - Din, Laily; Zakaria, Zuriati; Samsudin, Mohd Wahid; Brophy, Joseph; Toia, Robert F. (1988)
The steam volatile oil from the aerial parts of Hyptis suaveolens has been examined by combined GC-MS. Of the 70 components detected, 38 have been identified accounting for approximately 86% of the oil. ( β Caryophyllene was present to 41% and 1,8-cincole, terpinen-4-o 1, ex-bergamotene, sabinene and ex -copaene were the other major components. This oil appears to be chemically distinct from the one reported from H. suaveolens collected in South America.